Photoluminescence properties of rare earth (Nd, Yb, Sm, Pr)-doped CeO2 pellets prepared by solid-state reaction. Issue 27 (12th June 2015) - Balestrieri, Matteo; Colis, Silviu; Gallart, Mathieu; Schmerber, Guy; Ziegler, Marc; Gilliot, Pierre; Dinia, Aziz
Abstract : The luminescence of rare earths in CeO2 is sensitized by intrinsic Ce 3+ ions. Abstract : Several structural and optical properties of ceria (band gap, refractive index and lattice parameter) make this material very promising for applications in optoelectronics and photovoltaics. In this paper, we show that CeO2 can be efficiently functionalized by doping with trivalent rare earth ions to give rise to photon management properties. The trivalent ions can be successfully inserted by solid-state reaction of the elementary oxide powders. By combining the information obtained from the absorbance spectra with that of the PL excitation spectra, we demonstrate the presence of the trivalent ions in CeO2 and provide insight in the electronic level structure and transfer mechanism. In particular, we prove that both the complex absorption spectra and the energy transfer mechanisms cannot be fully explained without considering the presence of isolated Ce 3+ ions in CeO2 .